Stem Cell Therapy for Neonatal Hypoxic-Ischemic Encephalopathy - Gonzales-Portillo, Gabriel S.; Reyes, Stephanny; Aguirre, Daniela; Pabon, Mibel M.; Borlongan, Cesar V. (Frontiers in Neurology, 2014)
Treatments for neonatal hypoxic ischemic encephalopathy (HIE) have been limited. The aim of this paper is to offer translational research guidance on stem cell therapy for neonatal HIE by examining clinically relevant animal models, practical stem cell sources, safety and efficacy of endpoint assays, as well as a general understanding of modes of action of this cellular therapy. In order to do so, we discuss the clinical manifestations of HIE, highlighting its overlapping pathologies with stroke providing insights on the potential of cell therapy, currently investigated in stroke, for HIE. To this end, we draw guidance from recommendations outlined in Stem cell Therapeutics as an Emerging Paradigm for Stroke or STEPS, which have been recently modified to Baby STEPS to cater for the “neonatal” symptoms of HIE. These guidelines recognized that neonatal HIE exhibits distinct disease symptoms from adult stroke in need of an innovative translational approach that facilitates the entry of cell therapy in the clinic. Finally, new information about recent clinical trials, and insights into combination therapy are provided with the vision that stem cell therapy may benefit from available treatments, such as hypothermia, already being tested in children diagnosed with HIE.